2012
DOI: 10.1080/1359866x.2012.700043
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing Teaching (FIT)-Choice scale in a Dutch teacher education program

Abstract: This study examined the suitability of the FIT-Choice scale in a Dutch educational context among two cohorts of preservice teachers (Ns = 62, 89), surveyed at the end and the beginning of their one-year program respectively. The relationships between the motivations for becoming a teacher and concurrent commitment were examined, as well as the differences between the two cohorts. The factor analyses were consistent with the original FIT-Choice structure. The main motivation for becoming a teacher was the self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
78
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 20 publications
16
78
0
12
Order By: Relevance
“…Interview-based studies found the desire to help children, to make a positive difference in society, to experience personal growth (Struyven, Jacobs, & Dochy, 2013), and to experience high job satisfaction (Williams & Forgasz, 2009) as the most prevalent motives among teachers in addition to widespread attitudes of selflessness and altruism (May, Mand, Biertz, Hummers-Pradier, & Kruschinski, 2012). Additionally, studies using the factors influencing teaching (FIT) measurement revealed high levels of motivation to teach in those who desired to enhance social equity (Fokkens-Bruinsma & Canrinus, 2012) and had high levels of intrinsic career value (Klassen, Al-Dhafri, Hannok, & Betts, 2011) as well as social utility value (Lin, Shi, Wang, Zhang, & Hui, W 2012). In contrast, external factors including time for family, salary, status (Fokkens-Bruinsma & Canrinus, 2012), and self-expression (Lin et al, 2012) were lower in participants motivated to teach.…”
Section: Motivations To Teachmentioning
confidence: 99%
See 2 more Smart Citations
“…Interview-based studies found the desire to help children, to make a positive difference in society, to experience personal growth (Struyven, Jacobs, & Dochy, 2013), and to experience high job satisfaction (Williams & Forgasz, 2009) as the most prevalent motives among teachers in addition to widespread attitudes of selflessness and altruism (May, Mand, Biertz, Hummers-Pradier, & Kruschinski, 2012). Additionally, studies using the factors influencing teaching (FIT) measurement revealed high levels of motivation to teach in those who desired to enhance social equity (Fokkens-Bruinsma & Canrinus, 2012) and had high levels of intrinsic career value (Klassen, Al-Dhafri, Hannok, & Betts, 2011) as well as social utility value (Lin, Shi, Wang, Zhang, & Hui, W 2012). In contrast, external factors including time for family, salary, status (Fokkens-Bruinsma & Canrinus, 2012), and self-expression (Lin et al, 2012) were lower in participants motivated to teach.…”
Section: Motivations To Teachmentioning
confidence: 99%
“…Studies have found that those highly motivated to teach were also motivated by positive teaching and learning experiences (Fokkens-Bruinsma & Canrinus, 2012), a high perceived ability to teach (Klassen et al, 2011), positive experiences with adolescents or young people, positive training or instructing roles experience, and the feeling that teaching would coincide with their skill set, interests (Williams & Forgasz, 2009), and future goals (Richardson & Watt, 2006). Both the intrinsic and extrinsic motives to teach as well as the experienced self-efficacy and altruism of teachers presented in the literature suggest a nexus of meaning out of which teaching emerges as attractive and desirable to certain individuals.…”
Section: Motivations To Teachmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies using the factors influencing teaching (FIT) measurement revealed high levels of motivation to teach in those who desired to enhance social equity (Fokkens-Bruinsma & Canrinus, 2012) and had high levels of intrinsic career value (Klassen, Al-Dhafri, Hannok, & Betts, 2011) as well as social utility value (Lin, Shi, Wang, Zhang, & Hui, 2012). In contrast, external factors including time for family, salary, status (Fokkens-Bruinsma & Canrinus, 2012), and self-expression (Lin et al, 2012) were lower in participants motivated to teach.…”
Section: Motivations To Teachmentioning
confidence: 99%
“…Interview-based studies found the desire to help children, to make a positive difference in society, to experience personal growth (Struyven, Jacobs, & Dochy, 2013), and to experience high job satisfaction (Williams & Forgasz, 2009) as the most prevalent motives among teachers in addition to widespread attitudes of selflessness and altruism (May, Mand, Biertz, Hummers-Pradier, & Kruschinski, 2012). Additionally, studies using the factors influencing teaching (FIT) measurement revealed high levels of motivation to teach in those who desired to enhance social equity (Fokkens-Bruinsma & Canrinus, 2012) and had high levels of intrinsic career value (Klassen, Al-Dhafri, Hannok, & Betts, 2011) as well as social utility value (Lin, Shi, Wang, Zhang, & Hui, 2012). In contrast, external factors including time for family, salary, status (Fokkens-Bruinsma & Canrinus, 2012), and self-expression (Lin et al, 2012) were lower in participants motivated to teach.…”
Section: Motivations To Teachmentioning
confidence: 99%